Tungsten carbonitride substrate-based coherent heterostructure catalyst material and preparation method thereof

By growing Pt-based nanocatalysts with co-uniform heterostructures in situ on WCN substrate materials, the problem of decay of catalyst performance in electrocatalytic hydrogen evolution reaction is solved, and an efficient and stable hydrogen evolution reaction is achieved, which is better than the existing technology.

CN119710786AActive Publication Date: 2025-03-28BEIJING UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510088593.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-03-28
Estimated Expiration
2045-01-20

AI Technical Summary

Technical Problem

In the existing electrocatalytic hydrogen evolution reaction, the performance of the catalyst declines, resulting in low reaction efficiency and stability.

Method used

By growing Pt-based nanocatalysts with co-uniform heterostructures on tungsten carbon nitride (WCN) substrate materials in situ, a co-uniform interface structure between the catalyst and the substrate material is constructed, interface charge distribution and transfer are optimized, and catalyst activity and stability are improved.

Benefits of technology

The efficient electrocatalytic hydrogen evolution reaction of the catalyst is achieved, which significantly improves the reaction efficiency and long-term cycle stability, and is better than commercial Pt/C catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005250857410000011
    Figure HDA0005250857410000011
  • Figure HDA0005250857410000012
    Figure HDA0005250857410000012
  • Figure HDA0005250857410000013
    Figure HDA0005250857410000013
Patent Text Reader

Abstract

The invention discloses a coherent heterostructure catalyst material based on a tungsten carbonitride substrate and a preparation method of the coherent heterostructure catalyst material, and belongs to the field of catalysts. Preparing a solution containing platinum and doped metal salt, namely a solution A; preparing a reducing agent solution containing a surfactant, namely a solution B; the WCN substrate is placed in the solution B, the solution B is heated to 220-250 DEG C, then the solution A is dropwise added into the solution B step by step, a constant-temperature reaction is conducted till dropwise adding is completed, stirring and cooling are conducted to the room temperature, and Pt-based nano catalyst particles with the coherent heterostructure can be generated on the WCN nano structure in situ; the catalyst and a substrate material form a coherent interface structure, interface charge distribution and transfer are promoted, and then the activity and stability of the nano catalyst are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrocatalytic material technology preparation and application, and in particular to a catalyst composite thin film electrode electrocatalytic hydrogen evolution material with a coherent heterogeneous structure, and a synthesis method for its in-situ growth. Background Art

[0002] Electrocatalytic water splitting is a promising technology for producing clean hydrogen fuel. The development of cost-effective, efficient, and durable hydrogen evolution reaction (HER) electrocatalysts plays an important role in electrocatalytic water splitting. Platinum-based electrocatalysts exhibit good electrocatalytic activity in both acidic and alkaline media, but the economic cost limits their further application. Recent studies have shown that heterostructured electrocatalysts also show the potential for efficient electrocatalytic hydrogen evolution. The matching degree of the interface of heterostructured electrocatalysts affects their interfacial electronic structure, which in turn determines the kinetics and activity of the hydrogen evolution reaction. Therefore, it is of great significance and challenging to develop methods to construct coherent interfacial heterostructured electrocatalysts for electrocatalytic hydrogen evolution reaction. Summary of the invention

[0003] In response to the above defects or improvement needs of the prior art, the present invention provides a method for in situ synthesis of coherent heterostructured nanocatalyst composite thin film electrode materials, the purpose of which is to construct a coherent interface structure between the catalyst and the substrate material, promote interfacial charge distribution and transfer, and thereby enhance the activity and stability of the nanocatalyst, thereby solving the technical problem of performance degradation in the electrocatalytic process.

[0004] To achieve the above object, according to one aspect of the present invention, a method for preparing and synthesizing a coherent heterostructure catalyst composite electrode is provided, comprising the following steps:

[0005] (1) Platinum-containing salt and salt corresponding to the doped metal are placed in water, stirred and ultrasonically dispersed uniformly, and recorded as solution A;

[0006] (2) placing a reducing agent in a container, adding a small amount of a surfactant protective agent, and stirring until completely dissolved, which is recorded as solution B; triethylene glycol is used as a reducing agent and solvent to provide a reduction reaction environment for the subsequent metal precursor, and polyvinyl pyrrolidone (PVP) is added as a surfactant protective agent to increase the catalyst nucleation sites on the substrate material, making it easier for the catalyst crystals to grow in situ on the substrate;

[0007] (3) preparing or purchasing flaky tungsten carbonitride (WCN) as a substrate material;

[0008] Patent 202311680121.0 discloses a method for preparing a nanoscale high-conductivity tungsten carbonitride heterojunction film. According to the process described therein, tungsten carbonitride (WCN) with a high specific surface area is prepared as a substrate material for the subsequent in-situ growth of a Pt-based catalyst;

[0009] (4) placing the substrate in solution B, heating solution B to 220-250° C., then gradually dropping solution A into solution B, reacting at a constant temperature until the solution is completely dropped, stirring and cooling to room temperature, and then in-situ generating Pt-based nanocatalyst particles with a coherent heterostructure on the WCN nanostructure;

[0010] In the further step (1), the doping metal is one or more of copper, cobalt, nickel and zinc, preferably four of them; wherein the concentration of copper, cobalt, nickel and zinc is 1-20 times the concentration of platinum; and the concentration of platinum is 1-5 mM;

[0011] In step (2), 1 to 1.2 g of PVP is added to every 100 to 300 mL of triethylene glycol solution.

[0012] In step (4), each cm 2 The WCN substrate with an area of ​​1.37 mm2 corresponds to the in-situ growth of 5-20 μg of platinum. The loading amount of platinum is relatively low.

[0013] The coherent heterostructure catalyst material based on a tungsten carbonitride substrate obtained by the present invention is directly used as a hydrogen evolution reaction (HER) electrocatalytic electrode for water electrolysis to produce hydrogen.

[0014] Compared with the prior art, the present invention has the following advantages and significant effects:

[0015] (1) The present invention prepares for the first time a Pt-based nano-catalyst composite thin film electrode material with a coherent heterostructure (the interface between the prepared Pt-based catalyst and the WCN substrate material has a coherent relationship). This coherent interface structure will cause electron redistribution at the interface between the catalyst and the substrate material, forming a continuous electron conduction pathway, thereby adjusting the electronic structure of the catalyst to make it closer to the optimal state of the hydrogen evolution reaction.

[0016] (2) The interfacial coherent heterostructure proposed in the present invention achieves excellent crystal plane matching at the interface between the catalyst and the substrate, thereby improving the structural stability of the electrode material under long-term electrocatalytic reaction cycles.

[0017] (3) The interfacial coherent heterostructure proposed in the present invention produces a synergistic effect at the interface between the catalyst and the substrate. The substrate material can enrich electrons on its surface, adsorb hydrogen species (H*) in the dissociated solution, and participate in the hydrogen evolution reaction together with the catalyst, thereby improving the efficiency of the overall electrocatalytic hydrogen evolution reaction.

[0018] (4) The interfacial coherent heterostructure proposed in the present invention, the WCN substrate material can provide good electronic conductivity, while the catalyst can provide abundant active sites, and the combination of the two can achieve a more efficient hydrogen evolution reaction.

[0019] (5) The present invention significantly reduces the amount of precious metal platinum used by controlling the content of the precious metal platinum precursor or introducing the doping of four transition metal elements, namely cobalt, nickel, copper and zinc. At the same time, the combination of multiple elements can make the metal alloy catalyst have a controllable electronic structure and extremely excellent structural stability.

[0020] (6) The electrocatalytic hydrogen evolution performance exhibited by the material of the present invention is superior to the best commercially available platinum-carbon catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the technical solution of the present invention, the drawings required for use in the description of specific examples will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0022] Figure 1 This is a schematic diagram of the preparation and synthesis of the material described in the present invention.

[0023] Figure 2 Figure 2 is the X-ray diffraction pattern (XRD) of the catalyst material in situ grown on the tungsten carbonitride in all the examples of the present invention. Figure (b) is an enlargement of the dotted area in Figure (a). The dotted line in Figure (b) is the standard diffraction peak of platinum. It can be seen that the diffraction peak positions of the catalyst composite thin film electrode and the substrate are basically consistent, and the peak positions of the Pt-based catalyst and the substrate coincide.

[0024] Figure 3 This is a high-resolution transmission electron microscopy image (HRTEM) of the material PtCoNiCuZn / WCN described in Example 1 of the present invention and a distribution map (Mapping) of its corresponding elements. It can be seen that the particles are evenly distributed on the base material.

[0025] Figure 4 The figure in the figure is a characterization diagram of the atomic structure of a single nanoparticle of the PtCoNiCuZn / WCN catalytic material described in Example 1 of the present invention. The larger and brighter atoms in the figure are Pt, and the smaller and darker atoms are Co, Ni, Cu or Zn elements. From (a) and (b), it can be seen that the content of the noble metal atom Pt is significantly higher than that of the non-noble metal atom (Co, Ni, Cu or Zn, mainly because when the reducing agent is in-situ reduced to grow the metal on the substrate, the reducing agent has a greater reducing ability to Pt than Co, Ni, Cu or Zn, and it is also easy to grow in-situ on the substrate), and the two are arranged irregularly and randomly, thus forming a crystal structure of non-noble metal atoms doped with noble metals.

[0026] Figure 5This is a high-resolution transmission electron microscopy (HRTEM) image of the coherent heterostructure of the catalyst and substrate of the material described in Example 1 of the present invention, which corresponds to the XRD image. The interplanar spacings of the substrates WC(100) and WN(100) are and The interplanar spacing of the catalyst particles (111) is The interface mismatch between the two is 0.05<δ<0.5, which belongs to the category of coherence relationship.

[0027] Figure 6 The mass activity comparison diagram of the materials described in all examples of the present invention, specifically including Pt / WCN, PtCu / WCN, PtCoNiCuZn / WCN and commercial Pt / C (20%) catalysts, is a normalized mass activity comparison bar chart of precious metals when catalyzing hydrogen evolution reaction in 0.5 molar sulfuric acid solution, with a reversible hydrogen electrode (RHE) as the reference electrode. At an overpotential of 50mV, the precious metal mass activity of the material with the best performance shown in the present invention is 4.63A / mg (mass activity is a common performance comparison standard for precious metal-based catalysts, usually referring to the ratio of the current density of the electrode material per unit area at a certain overpotential to the mass of the catalyst thereon. The mass activity described in this patent is actually at an overpotential of 50mV, and its current density unit is mA / cm 2 The loading amount of precious metal in the catalyst per unit area is 8.8 μg / cm 2 , so the ratio of the two is converted in units of ampere / mg), which is 22 times that of the commercial Pt / C (20%) catalyst. The above proves that the material of the present invention has a high utilization rate of precious metals and excellent performance when used as a catalyst for electrocatalytic hydrogen evolution reaction.

[0028] Figure 7 The chronopotentiometric curve of the electrocatalytic hydrogen evolution reaction of the material of Example 1 of the present invention in a 0.5 mol / L sulfuric acid solution. It can be seen that compared with the commercial Pt / C catalyst, the potential of the material of the present invention has almost no decay after 300 hours. Therefore, the material of the present invention has higher stability. DETAILED DESCRIPTION

[0029] The technical scheme of the present invention is described clearly and completely below in conjunction with specific examples. Obviously, the described embodiments are only some examples of the present invention, rather than all examples. Specific conditions are not indicated in the examples, and the experimental methods used are usually carried out according to conventional laboratory conditions, conditions described in the manual, or according to the conditions recommended by the manufacturer. The general equipment, materials, reagents, etc. used can be obtained through commercial channels without special instructions. In addition, based on the examples of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the protection scope of the present invention.

[0030] Example 1

[0031] The catalyst composite thin film electrode material with coherent heterostructure is prepared by the following steps:

[0032] Step (1), preparing a precursor solution, which contains a mixed solution of 2 mM chloroplatinic acid hexahydrate, 20 mM cobalt chloride hexahydrate, 20 mM nickel chloride hexahydrate, 20 mM cupric chloride dihydrate, and 20 mM zinc chloride, stirring and ultrasonicating to mix evenly.

[0033] Step (2), prepare the reaction solution, add 100-300 mL of triethylene glycol solution into the reaction container, add 1-1.2 g of PVP, stir continuously until it is completely dissolved, and obtain a reducing mixed reaction solution containing a surfactant. The purpose of triethylene glycol is to create conditions for various metal ions in the above-mentioned metal precursor solution to form corresponding metallic atoms, and the addition of a surfactant can improve the hydrophilicity / hydrophobicity of the base material and increase the active sites of the base material and the nucleation sites of the catalyst atoms.

[0034] Step (3), cut the substrate WCN sheet into 1×1 cm and place it in the mixed reaction solution obtained in step (2), heat the reaction container to 230°C in a magnetic stirring oil bath, and then stir 90 mL of the precursor solution in step (1) at 1 mL min -1 The reaction solution is added drop by drop continuously at a dripping speed, and the mixture is stirred vigorously during the process. The purpose of adding drop by drop is that the ionic state of the metal precursor can be fully reduced to the metallic state under the action of the reducing agent. The purpose of stirring vigorously is to disperse the atoms reduced to the metallic state in time and inhibit their agglomeration in the solution.

[0035] Step (4), according to the operation steps of step (3), after the precursor solution is dripped down, the constant temperature of 230°C is ended, and it is naturally cooled to room temperature, and stirring is kept during the period. Finally, the in-situ grown PtCoNiCuZn / WCN interface coherent heterostructure catalyst composite electrode can be obtained.

[0036] Figure 2 The X-ray diffraction pattern (XRD) of the catalytic material obtained in this example is shown in Figure 2. Compared with the WCN substrate, the dotted line corresponds to the standard diffraction peak of metallic Pt, which is basically consistent with the diffraction peak intensity of the substrate WCN, indicating the low loading of the catalyst and the crystal plane spacing similar to that of the substrate. The slight shift in the peak position is caused by the doping of transition elements.

[0037] Figure 3The high-resolution transmission electron microscopy image (HRTEM) of the catalytic material obtained in this example and its corresponding element energy spectrum distribution map (Mapping) are shown, which clearly shows that the particles are uniformly loaded on the substrate and the elements are uniformly distributed among the nanoparticles without phase separation.

[0038] Figure 4 The atomic structure characterization diagram of a single nanoparticle of the catalytic material obtained in this example is shown in Figures (a) and (b). It can be seen that the larger and brighter Pt atoms are more abundant than the smaller and darker Co, Ni, Cu or Zn atoms, and the two are arranged randomly and irregularly, constituting the doping of non-precious metal elements into the precious metal structure.

[0039] Figure 5 The high-resolution transmission electron microscopy (HRTEM) image of the coherent heterostructure of the catalytic material obtained in this example is shown in FIG. The interface mismatch between the substrate and the catalyst corresponding to the area marked by the dotted line belongs to the range of the coherent relationship, which corresponds to the XRD pattern.

[0040] Figure 6 The mass activity diagram of the catalytic material obtained in this example is shown in FIG. 5 . At an overpotential of 50 mV vs. RHE, the mass activity is about 22 times higher than that of the commercial Pt / C (20%) catalyst.

[0041] Figure 7 The chronopotentiometry result diagram of the catalytic material obtained in this example is shown in FIG. 1 . It can be seen that, compared with the curve of Pt / C (20%), the overpotential of the material in this example hardly decays after a long cycle of 300 hours.

[0042] Example 2

[0043] Referring to the method in Example 1, a catalyst composite thin film electrode material having a coherent heterogeneous structure is prepared by the following steps:

[0044] Step (1), preparing a precursor solution containing a mixed solution of 2 mM chloroplatinic acid hexahydrate and 20 mM cupric chloride dihydrate, stirring and ultrasonicating to mix evenly.

[0045] Step (2), preparing a reaction solution, adding 100-300 mL of triethylene glycol solution into a reaction container, adding 1-1.2 g of PVP, and continuously stirring until it is completely dissolved to obtain a reducing mixed reaction solution containing a surfactant.

[0046] Step (3), place a 1×1 cm substrate WCN sheet in the mixed reaction solution obtained in step (2), heat the reaction container to 230°C in a magnetic stirring oil bath, and then stir 90 mL of the precursor solution in step (1) at 1 mL min -1The mixture was added drop by drop into the reaction solution continuously while stirring vigorously.

[0047] Step (4), according to the operation steps of step (3), after the precursor solution is dripped down, the constant temperature of 230°C is ended, and it is naturally cooled to room temperature, and stirring is kept during the period. Finally, an in-situ grown PtCu / WCN interface coherent heterostructure catalyst composite electrode can be obtained.

[0048] Figure 2 The X-ray diffraction pattern (XRD) of the catalytic material obtained in this example is shown in Figure 2. Compared with the WCN substrate, the dotted line corresponds to the standard diffraction peak of metallic Pt, which is basically consistent with the diffraction peak intensity of the substrate WCN, indicating the low loading of the catalyst and the crystal plane spacing similar to that of the substrate. The slight shift in the peak position is caused by the doping of transition elements.

[0049] Figure 6 The mass activity diagram of the catalytic material obtained in this example is shown in FIG. 5 . At an overpotential of 50 mV vs. RHE, the mass activity is about 7.4 times higher than that of the commercial Pt / C (20%) catalyst.

[0050] Example 3

[0051] Referring to the method in the above example, a catalyst composite thin film electrode material having a coherent heterogeneous structure is prepared by the following steps:

[0052] Step (1), preparing a precursor solution containing 2 mM chloroplatinic acid hexahydrate solution, stirring and ultrasonicating, and mixing uniformly.

[0053] Step (2), preparing a reaction solution, adding a triethylene glycol solution into a reaction container, adding 1 to 1.2 grams of PVP, and continuously stirring until it is completely dissolved, to obtain a reducing mixed reaction solution containing a surfactant.

[0054] Step (3), placing substrate WCN sheets of different sizes in the mixed reaction solution obtained in step (2), heating the reaction container to 230°C in a magnetic stirring oil bath, and then stirring the precursor solution in step (1) at 1 mL min -1 The mixture was added drop by drop into the reaction solution continuously while stirring vigorously.

[0055] Step (4), according to the operation steps of step (3), after the precursor solution is dripped down, the constant temperature of 230°C is ended, and it is naturally cooled to room temperature, and stirring is kept during the period. Finally, an in-situ grown Pt / WCN interface coherent heterostructure catalyst composite electrode can be obtained.

[0056] Figure 2The X-ray diffraction pattern (XRD) of the catalytic material obtained in this example is shown in Figure 2. Compared with the WCN substrate, the dotted line corresponds to the standard diffraction peak of metallic Pt, which is basically consistent with the diffraction peak intensity of the substrate WCN, indicating the low loading of the catalyst and the crystal plane spacing similar to that of the substrate. The slight shift in the peak position is caused by the doping of transition elements.

[0057] Figure 6 The mass activity diagram of the catalytic material obtained in this example is shown in FIG. 5 . At an overpotential of 50 mV vs. RHE, the mass activity is about 4.9 times higher than that of the commercial Pt / C (20%) catalyst.

[0058] The above are specific implementation cases described in the present invention.

[0059] The experimental data shown in the accompanying drawings fully demonstrate the excellent performance of the coherent heterostructure catalyst of the present invention, which has greatly surpassed the current commercial Pt / C catalyst in many physical and chemical properties. It is a major breakthrough in the field of electrocatalytic materials and has considerable prospects in practical applications.

Claims

1. A method for preparing a coherent heterostructure catalyst material based on a tungsten carbonitride substrate, characterized in that: The following steps are involved: (1) Platinum-containing salt and salt corresponding to the doped metal are placed in water, stirred and ultrasonically dispersed uniformly, and recorded as solution A; (2) placing a reducing agent in a container, adding a small amount of a surfactant protective agent, and stirring until completely dissolved, which is recorded as solution B; triethylene glycol is used as a reducing agent and solvent to provide a reduction reaction environment for the subsequent metal precursor, and polyvinyl pyrrolidone (PVP) is added as a surfactant protective agent to increase the catalyst nucleation sites on the substrate material, making it easier for the catalyst crystals to grow in situ on the substrate; (3) preparing flake tungsten carbonitride (WCN) as a substrate material; (4) placing the substrate in solution B, heating solution B to 220-250°C, then gradually dropping solution A into solution B, reacting at a constant temperature until the solution is completely dropped, stirring and cooling to room temperature, thereby in situ generating Pt-based nanocatalyst particles with a coherent heterostructure on the WCN nanostructure.

2. A method for preparing a coherent heterostructure catalyst material based on a tungsten carbonitride substrate according to claim 1, characterized in that: Flaky tungsten carbonitride (WCN) with a high specific surface area is prepared using the preparation method disclosed in 202311680121.

0.

3. The method for preparing a coherent heterostructure catalyst material based on a tungsten carbonitride substrate according to claim 1, characterized in that: In step (1), the doping metal is one or more of copper, cobalt, nickel and zinc, preferably four of them; wherein the concentration of copper, cobalt, nickel and zinc is 1-20 times the concentration of platinum; and the concentration of platinum is 1-5 mM.

4. According to the method for preparing a coherent heterostructure catalyst material based on a tungsten carbonitride substrate as claimed in claim 1, in step (2), 1 to 1.2 grams of PVP are added for every 100 to 300 mL of triethylene glycol solution.

5. The method for preparing a coherent heterostructure catalyst material based on a tungsten carbonitride substrate according to claim 1, wherein in step (4), each cm 2 The area of ​​tungsten carbonitride (WCN) substrate corresponds to the in-situ growth of 5 to 20 μg of platinum.

6. A coherent heterostructure catalyst material based on a tungsten carbonitride substrate prepared according to the method described in any one of claims 1 to 5.

7. Use of a coherent heterostructure catalyst material based on a tungsten carbonitride substrate prepared by the method according to any one of claims 1 to 5, directly as a hydrogen evolution reaction (HER) electrocatalytic electrode for water electrolysis to produce hydrogen.

Citation Information

Patent Citations

  • Preparation method of nanoscale high-conductivity tungsten carbonitride heterojunction film

    CN117661022A

  • Platinum-based composite catalyst for alkaline electrolyzed water and preparation method of platinum-based composite catalyst

    CN117926339A

  • MOF-derived nitrogen cobalt heterogeneous nanobox electrocatalyst, preparation method therefor, and use thereof

    WO2024234835A1